Implementing the Aberdeen Agenda in South Asia: A regional training program for elected members (Commonwealth Journal of Local Governance, 2009)
In 2005 CLGF members adopted the Aberdeen Agenda: Commonwealth Principles on Good Practice for Local Democracy and Good Governance. The twelve Principles were developed at the CLGF’s biennial conference in March 2005 and were subsequently forwarded to Commonwealth Heads of Government, who also adopted them as part of their commitment to fundamental political values when they met the following November. Since then members of CLGF have used them in a variety of different ways – to support their own policy making, to enhance their lobbying and advocacy work, and in some cases, notably in Pakistan and Uganda (see CJLG Issue 2), to undertake a selfassessment of the health of their systems of local democracy and governance.